Cooling Performance Characteristics of the Stack Thermal Management System for Fuel Cell Electric Vehicles under Actual Driving Conditions - Ho-Seong Lee (Energies, 2016)
The cooling performance of the stack radiator of a fuel cell electric vehicle was evaluated under various actual road driving conditions, such as highway and uphill travel. The thermal stability was then optimized, thereby ensuring stable operation of the stack thermal management system. The coolant inlet temperature of the radiator in the highway mode was lower than that associated with the uphill mode because the corresponding frontal air velocity was higher than obtained in the uphill mode. In both the highway and uphill modes, the coolant temperatures of the radiator, operated under actual road driving conditions, were lower than the allowable limit (80 °C); this is the maximum temperature at which stable operation of the stack thermal management system of the fuel cell electric vehicle could be maintained. Furthermore, under actual road driving conditions in uphill mode, the initial temperature difference (ITD) between the coolant temperature and air temperature of the system was higher than that associated with the highway mode; this higher ITD occurred even though the thermal load of the system in uphill mode was greater than that corresponding to the highway mode. Since the coolant inlet temperature is expected to exceed the allowable limit (80 °C) in uphill mode under higher ambient temperature with air conditioning system operation, the FEM design layout should be modified to improve the heat capacity. In addition, the overall volume of the stack cooling radiator is 52.2% higher than that of the present model and the coolant inlet temperature of the improved radiator is 22.7% lower than that of the present model.